2023
DOI: 10.3390/biomedicines11112885
|View full text |Cite
|
Sign up to set email alerts
|

Active Matrix Metalloproteinase-8 (aMMP-8) Versus Total MMP-8 in Periodontal and Peri-Implant Disease Point-of-Care Diagnostics

Ismo T. Räisänen,
Nur Rahman Ahmad Seno Aji,
Dimitra Sakellari
et al.

Abstract: Active matrix metalloproteinase-8 (aMMP-8) is a promising biomarker candidate for the modern periodontal and peri-implant disease diagnostics utilizing the chairside/point-of-care oral fluid technologies. These rapid biomarker analysis technologies utilize gingival crevicular fluid (GCF), peri-implant sulcular fluid (PISF), or mouth rinse as the oral fluid matrices that can be collected patient-friendly and non-invasively without causing bacteremia. aMMP-8, but not total or latent proMMP-8, has been shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…This is in line with previous studies that showed clinical attachment loss occurring due to the RT [5,28,30]. MMP-8 is the most prevalent collagenolytic protease in the diseased periodontium and aMMP-8 the major mediator of periodontitis [15]. As the aMMP-8 levels stayed elevated after RT, it is possible that collagenolytic activity and the burden of aMMP-8 predisposes tissue for further periodontal damage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with previous studies that showed clinical attachment loss occurring due to the RT [5,28,30]. MMP-8 is the most prevalent collagenolytic protease in the diseased periodontium and aMMP-8 the major mediator of periodontitis [15]. As the aMMP-8 levels stayed elevated after RT, it is possible that collagenolytic activity and the burden of aMMP-8 predisposes tissue for further periodontal damage.…”
Section: Discussionsupporting
confidence: 91%
“…With periodontal disease being increasingly recognized as a contributor in the pathophysiology of several systemic diseases, cancers, as well as risk factor for osteoradionecrosis, it is important to monitor and recognize worsened periodontal status after RT [31,32]. Periodontitis can be detected in real time with chairside/point-of-care aMMP-8 immunotest visually (−/+) and/or quantitatively in 5 min [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A chairside/point-of-care oral fluid test is an immunofluorescent or immunochromatographic assay employing different antibodies to detect both PMN and non-PMN-type MMP-8 isoforms, which may or not recognize different epitopes of the two isoforms [ 264 , 270 ]. This tool can be used for early disease detection as well as monitoring progression and evaluating therapeutic effects [ 271 ]. The current grading parameters allow us only to predict whether it is likely that the periodontal breakdown would occur in the future, but not the exact time when it would occur [ 272 ].…”
Section: The Extracellular Matrix Of the Periodontium And The Role Of...mentioning
confidence: 99%
“…For example, matrix metalloproteinases, namely MMP-8 and MMP-9, are significantly elevated in the GCF of periodontitis patients. [35][36][37] They are markers of collagen degradation, a classic symptom of periodontal disease. 35 However, it has been shown that it is the active form of MMP-8 (aMMP-8) that is a relevant biomarker for periodontitis and periimplantitis rather than the total or latent proMMP-8.…”
Section: Clinical Care Requirements For Poc Devicesmentioning
confidence: 99%